Peningkatan Pengetahuan Melalui Pelatihan Pemanfaatan Limbah Kulit Nenas Sebagai Bahan Pembuatan Sabun Cuci Piring - Vonny Indah Sari; Vivin Jenika Putri; Anania Rahmah (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2022)
Generally, pineapple waste such as pineapple peel is not used properly and is considered as garbage that should be thrown away. In fact, from the results of phytochemical tests, pineapple peel contains flavanoid, tannin and saponin compounds and contains compounds that have the potential as anti-bacterial. One of the uses of pineapple peel waste is as the main ingredient in making dish soap. Dish soap produced from processed waste of pineapple peel and lime slices has a fresh aroma and good washing power and is gentle on hands. The purpose of this service is to increase the knowledge of the community of RW 12 Tangkerang Tengah Village in utilizing pineapple skin waste that is widely scattered in Pekanbaru City where pineapple is one of the mainstays of agricultural products produced from Pekanbaru, especially Kualu Nenas Village. With this training, it is hoped that the community can utilize pineapple waste into more useful products and furthermore housewives of RW 12 Tangkerang Tangah Village can make their own dish soap for their own use or for sale.